Роль публічних виступів для IT-спеціаліста - Лега, Є. С. (ХНУРЕ, 2020)
Many people mistakenly believe that it is important to be a good specialist in order to succeed at work. It is impossible to move in the career ladder, only due to professional skills. Often people forget about soft skills. Public speaking, knowleges about time managment and teamwork, all this things are basic skills that a potentially good specialist should have. Public speaking helps to develop not only the ability to speak, but also leadership qualities, which will help in the future to move from a usual specialist to a manager. This article will discuss the benefits of public speaking and how to prepare for them.
Keywords: філософія; IT-спеціаліст